Determination of reactive oxygen species in nasal polyps - (:unkn) unknown (INT RHINOLOGIC SOC, 2005)
A strong relationship between tissue damage and reactive oxygen species (ROS) has been established by previous studies. The aim of the current study was to evaluate the presence of ROS in nasal polyps (NP) by measuring luminol and lucigenin amplified chemiluminescence (CL). Three groups of specimens were studied. Group 1 composed of NPs of 15 patients, and group 2 constituted of healthy appearing nonpolypoid nasal mucosa of the same patients. Group 3 specimens (control group) were obtained from 15 patients who underwent septoplasty and/or inferior turbinectomy operations, and detected to be free of rhinosinusitis. None of the patients had a history of allergy, asthma, or aspirin sensitivity, and all patients showed negative results to a skin prick test. The ROS levels were measured directly with luminol and lucigenin amplified CL. CL measurements revealed significant differences between ROS constituents of NP (group 1) and control (group 3) tissue samples. CL measurements of healthy appearing nonpolypoid nasal mucosa (group 2) of the NP patients revealed values that were scattered between the values of the other two groups. Although insignificant, ROS levels of the nonpolypoid nasal mucosa (group 2) were found to be higher than normal controls (group 3). In this study, ROS levels of NP tissue samples were directly measured. In our study, by measuring high ROS levels in NP samples, a strong relationship between tissue damage in NPs and ROS has been demonstrated, and the contribution of ROS in the pathophysiology of nasal polyposis has been emphasized.
Keywords: nasal polyp; reactive oxygen species; free radicals; chemiluminescence; CHRONIC RHINOSINUSITIS; FREE-RADICALS; OTITIS-MEDIA; NITRIC-OXIDE; EOSINOPHILIA; MUCOSA; CHEMILUMINESCENCE; INFLAMMATION; SINUSITIS; MEDICINE